2020
DOI: 10.1101/2020.11.11.378208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactions between two QTLs for time to anthesis on spike development and fertility in wheat

Abstract: Earliness per se (Eps) genes are reported to be important in fine-tuning flowering time in wheat independently of photoperiod (Ppd) and vernalisation (Vrn). Unlike Ppd and Vrn genes, Eps have relatively small effects and their physiological effect along with chromosomal position are not well defined. We evaluated eight lines derived from crossing Paragon and Baj (late and early flowering respectively), vernalisation insensitive, to study the detailed effects of two newly identified QTLs, Eps-7D and Eps-2B and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…However, the NILs would have sensitive alleles in the Ppd-1 loci on the A and/or B genome. Indeed, we could not discard that a new Eps-2B could actually be Ppd-B1 [ 40 ]. These genes produce responses that are frequently less noticeable than Ppd-D1 , but still significant [ 8 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the NILs would have sensitive alleles in the Ppd-1 loci on the A and/or B genome. Indeed, we could not discard that a new Eps-2B could actually be Ppd-B1 [ 40 ]. These genes produce responses that are frequently less noticeable than Ppd-D1 , but still significant [ 8 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently an Eps QTL on chromosome 7D was identified in wheat which was known to influence time to heading [ 40 ]. Four NILs were generated from the cross Paragon (a modern UK commercial cultivar [ 41 ] and Baj (a CIMMYT cultivar, used frequently as check [ 42 ], both of which are spring type with no requirements of vernalisation.…”
Section: Introductionmentioning
confidence: 99%
“…This Eps-7D interacted with temperature [ 1 ] and Eps-2B [ 16 ], and the interaction effect have been shown to be effective well beyond the duration of developmental phases. Our findings suggest that it is not only important to study every newly identified Eps gene (simply because although they are all named equally, the mechanisms by which they actually modify time to anthesis may be quite different), but it is also necessary to evaluate their functions under varying backgrounds of other important genetic factors affecting wheat development to ensure repeatability of their effect and their application.…”
Section: Discussionmentioning
confidence: 99%
“…At least in part, the ambiguity of the results reported in the literature may well reflect the fact that the mechanism of each Eps gene could be quite different from one another, beyond the fact that all affect time to heading/anthesis (by definition). Final leaf number (FLN), phyllochron, plastochron, spikelet number, floret development patterns and developmental phases can be affected or not depending on the specific Eps gene studied [ 7 , 8 , 9 , 13 , 14 , 15 , 16 ]. Therefore, it is important to study and evaluate each novel Eps along with their interactions with the other genetic factors (involved in complex network of genes altering the life cycle of wheat) and the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation